Business Agility & Strategic Management. Parametric Strategic Management Concept Meets Agile-Methods II - Alexander OBYDENOV (Communications of International Proceedings, 2020)
We are developing an idea that Parametric Strategic Management represents business-agility of organizations very well. Moreover, Agile methods comply with the emergent strategy concept quite isomorphically, and follows it in a consistent manner. Renunciation of strategic planning in management of organizational development happens to a significant degree in that context. At the same time, inasmuch as it remains it takes on new, more flexible forms. The concept of self-organization management? which essentially appears to be Parametric Strategic Management, holds a special place in such trends.. In a case study of a Russian teal supermarket chain «VkusVille», we analyze, how such management can be practically applied. That case, as well as exploring limits and necessary conditions for implementation of managed self-organization, indicate that Parametric management is relevant for business practice.
Keywords: business agility; agile management; parametric strategic management; managed self-organization